ANTHROPOCENTRIC APPROACH TO SLANG AS A LINGUISTIC PHENOMENON - Abdullaev Marks Kamilzhanovich (TILSHUNOSLIKDA ANTROPOSENTRIZM: YANGI YONDASHUVLAR VA TADQIQOTLAR MAVZUSIDAGI RESPUBLIKA ILMIY-AMALIY ANJUMAN, 2026)
This article examines slang as a cognitively and socially embedded linguistic phenomenon through the lens of the anthropocentric paradigm. Drawing on conceptual metaphor theory and mental model analysis, the study demonstrates that slang functions not as linguistic deviance but as a systematic expression of human cognitive and evaluative activity. Comparative material from Spanish and Russian slang corpora reveals universal anthropocentric mechanisms alongside culturally specific metaphorical mappings.